Probabilistic whole life cycle greenhouse gas displacement factors for timber frame house external walls - William Horan; David Styles; Song Ge; Patrick J. McGetrick; Michael Quilligan (Building and Environment, 2026)

Influence of field beans (Vicia faba L.) on yield and environmental footprint of following spring barley (Hordeum vulgare L.) crops - Umut Kartal; Colm Duffy; Sophie Saget; Frances Sandison; Andrew Christie; Cathy Hawes; Becky Howard; Roger Vickers; Dimitrios Savvas; David Styles; Pietro P. M. Iannetta (Plant and Soil, 2026)
Background and Aims The urgent need to reduce greenhouse gas emissions has increased interest in legume-based cropping systems. Among the various crop-legume species available, the cool-season species Vicia faba L. (cv. minor; field beans) has attracted significant interest. Assessment of the environmental impact reduction of field beans in a crop-sequence (rotation) is understudied. Methods Data from a long term (2009–2023) field bean experimental platform (the Centre for Sustainable Cropping, CSC; James Hutton Institute, Scotland, UK) were analysed using attributional life cycle assessment (aLCA). This focused on elaborating the impacts of a spring field bean to spring barley ( Hordeum vulgare L.) cropping sequence compared with a spring barley to spring barley cropping sequence. Results Field beans decreased the environmental impact of spring barley production in four of the five two-year crop-sequence periods, with mean impact reductions of approximately 25% across sequences. Spring barley grain yields tended to increase following field beans under drought conditions (2022). A combined index analysis indicated that humidity, maximum temperature, and previous field bean yields were the strongest determinants of spring barley production. Conclusions The integration of field beans to cereal-dominated rotations may be of interest to major industries who seek to improve value chain sustainability, whilst ensuring crop-sequence yields are climate-impact resilient.

Cultural embeddedness and heterogeneity in farmer responses to agricultural transition in the Irish beef suckler sector - Sarah J. Mannion; Noel Ndlovu; Peter C. McKeown; David Styles; Charles Spillane (Journal of Rural Studies, 2026)

Environmental impact of the total chemical synthesis of barettin - Sophie Saget; Juan Ortega-Vidal; Olivier P. Thomas; David Styles (Journal of Cleaner Production, 2026)

Correction: Toward climate-smart beef cattle: quantifying emissions from genetic resources - Natalia Matiz-Rubio; Alejandro Ruden; Ricardo González-Quintero; Ciniro Costa; David Styles; Jacobo Arango (The International Journal of Life Cycle Assessment, 2026)

Critical evaluation of prospective biorefinery configurations to deliver a circular, climate neutral economy - Andrés Martínez-Arce; Vincent O'Flaherty; David Styles (Resources, Conservation and Recycling, 2026)

Techno-Economic assessment of Energy–Optimised grass biomethane and biofertilizer production simulated with Aspen plus and pinch technology - Milad Motaghi; Pedram Vousoughi; Abolghasem Kazemi; David Styles; Kenneth A. Byrne (Bioresource Technology, 2026)

On the interpretation of biogenic carbon flows in livestock LCAs: A comment on - Andre M. Mazzetto; Aaron T. Simmons; Beverley Henry; Christophe d'Abbadie; David Styles; Göran Berndes; Maartje Sevenster; Matthew T. Harrison; Richard Eckard; Warwick B. Badgery; Annette Cowie (Agricultural Systems, 2026)

A top-down approach in developing embodied carbon caps: Case study of the Irish residential sector - Song Ge; David Styles; Conan O’Ceallaigh; Patrick J. McGetrick (Energy and Buildings, 2026)

Toward climate-smart beef cattle: quantifying emissions from genetic resources - Natalia Matiz-Rubio; Alejandro Ruden; Ricardo González-Quintero; Ciniro Costa; David Styles; Jacobo Arango (The International Journal of Life Cycle Assessment, 2026)

Environmental assessment of anaerobic digestion within net-zero and policy-aligned AFOLU sector futures - Pedram Vousoughi; Andres Martinez Arce; George Bishop; Daniel Henn; Colm Duffy; David Styles; Kenneth A. Byrne (Journal of Cleaner Production, 2026)

Optimizing selective breeding of livestock and forage crops to reduce the environmental impacts of grass-based dairy production by combining life cycle assessment and machine learning - Noel Ndlovu; David Styles; Jefkine Kafunah; Mukund Narayanan; Luis Felipe Quiroz; Nikita Gondalia; Galina Brychkova; Peter C. McKeown; Charles Spillane (Science of The Total Environment, 2025)

Improving biogenic carbon and land use accounting for construction wood - William Horan; Michael Quilligan; George Bishop; David Styles (Resources, Conservation and Recycling, 2025)

IEA Bioenergy: Update 76 - David Styles; Göran Berndes (Biomass and Bioenergy, 2025)

Exploring the frontier of bovine protein production within territorial net zero emission targets - Daniel Henn; Colm Duffy; James Humphreys; James Gibbons; Emma Buckley; Kenneth A. Byrne; David Styles (Science of The Total Environment, 2025)

Multi-disciplinary investigation identifies increased potency of ethyl-parathion inhaled within a soil-dust matrix to cause acetylcholinesterase-dependent molecular impacts - Kurt A. Gust; Saroj K. Amar; Chet P. Gut; Renee M. Styles; Ranju R. Karna; R. Arden James; David M. Holtzapple; Joshua.L. Stricker; Shawn M. McInturf; Elizabeth A. Phillips; Cary Honnold; Xiao Luo; et al. (Environmental Toxicology and Pharmacology, 2025)

Lowering the greenhouse gas and ammonia emissions from grassland-based dairy production - Owen Cashman; Imelda Casey; Marion Sorley; Patrick Forrestal; David Styles; David Wall; William Burchill; James Humphreys (Agricultural Systems, 2025)

Comparative Life Cycle Assessment of alternative winter salad value chains supplying the United Kingdom - Sophie Saget; David Styles; Michael Williams (Science of The Total Environment, 2024)

Assessing the environmental footprint of alternative green biorefinery protein extraction techniques from grasses and legumes - James Gaffey; Andres Arce Matinez; Thalles Allan Andrade; Morten Ambye-Jensen; George Bishop; Maurice N. Collins; David Styles (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Nutritional value and environmental footprint of muffins made with green-lentil flour - Rafaela Geraldo; Carla S. Santos; David Styles; Sérgio Sousa; Elisabete Pinto; Delminda Neves; Marta W. Vasconcelos (Journal of Cleaner Production, 2024)

GeoGOBLIN: A catchment-scale land balance model for assessment of climate mitigation pathways considering environmental trade-offs for multiple impact categories - Colm Duffy; Daniel Henn; David Styles; Gregory G. Toth; Remi Prudhomme; Pietro P.M. Iannetta; Ken Byrne (Environmental Modelling & Software, 2024)

State-of-the-art in assessing the environmental performance of anaerobic digestion biorefineries - Andrés Martínez-Arce; Vincent O'Flaherty; David Styles (Resources, Conservation and Recycling, 2024)

Review of methodological decisions in life cycle assessment (LCA) of biorefinery systems across feedstock categories - James Gaffey; Maurice N. Collins; David Styles (Journal of Environmental Management, 2024)

Cattle production strategies to deliver protein with less land and lower environmental impact - Daniel Henn; Colm Duffy; James Humphreys; James Gibbons; Kenneth A. Byrne; David Styles (Journal of Environmental Management, 2024)

Net Zero requires ambitious greenhouse gas emission reductions on beef and sheep farms coordinated with afforestation and other land use change measures - Louise C. McNicol; Non G. Williams; Dave Chadwick; David Styles; Robert M. Rees; Rachael Ramsey; A. Prysor Williams (Agricultural Systems, 2024)

A tasty solution to packaging waste? Life cycle assessment of edible coffee cups - Keteki Anand; Andrés Martinez Arce; George Bishop; David Styles; Colin Fitzpatrick (Resources, Conservation and Recycling, 2024)

Factors influencing the carbon footprint of milk production on dairy farms with different feeding strategies in western Europe - Marion Sorley; Imelda Casey; David Styles; Pilar Merino; Henrique Trindade; Martin Mulholland; Cesar Resch Zafra; Ray Keatinge; André Le Gall; Donal O'Brien; James Humphreys (Journal of Cleaner Production, 2024)

Improved representation of cattle herd dynamics for bio-physical modelling of pathways to a climate neutral land sector - Daniel Henn; James Humphreys; Colm Duffy; James Gibbons; David Styles (Agricultural Systems, 2023)

Environmental and land use consequences of replacing milk and beef with plant-based alternatives - Marcela Porto Costa; Sophie Saget; Beate Zimmermann; Eckart Petig; Elisabeth Angenendt; Robert M. Rees; David Chadwick; James Gibbons; Shailesh Shrestha; Michael Williams; David Styles (Journal of Cleaner Production, 2023)

Water sector resilience in the United Kingdom and Ireland: The COVID-19 challenge - Nathan L. Walker; David Styles; A. Prysor Williams (Utilities Policy, 2023)

Optimising sustainability: Circular pathways for Scotch Whisky distillery co-products - Colm Duffy; David Styles; Isabel Schestak; Kenneth Macgregor; Frances Jack; Daniel Henn; Kirsty Black; Pietro P.M. Iannetta (Journal of Cleaner Production, 2023)

Heat recovery and water reuse in micro-distilleries improves eco-efficiency of alcohol production - Isabel Schestak; Jan Spriet; Kirsty Black; David Styles; Maria Faragò; Martin Rygaard; A. Prysor Williams (Journal of Environmental Management, 2023)

Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands - Benjamin W. J. Freeman; Chris D. Evans; Samuel Musarika; Ross Morrison; Thomas R. Newman; Susan E. Page; Giles F. S. Wiggs; Nicholle G. A. Bell; David Styles; Yuan Wen; David R. Chadwick; Davey L. Jones (Global Change Biology, 2022)
Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of ~2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation.

Optimized ratoon rice system to sustain cleaner food production in Jianghan Plain, China: a comprehensive emergy assessment - Zijuan Ding; Ren Hu; David Styles; Xiaolong Wang; Yingbing Tian; Yuxian Cao; Jun Hou (Environmental Science and Pollution Research, 2022)

Chemical and physical heterogeneity within native gold: implications for the design of gold particle studies - Robert John Chapman; David Archibald Banks; Michael Thomas Styles; Richard David Walshaw; Sandra Piazolo; Daniel Joseph Morgan; Matthew Russel Grimshaw; Carl Peter Spence-Jones; Thomas James Matthews; Olga Borovinskaya (Mineralium Deposita, 2021)
Studies of populations of gold particles are becoming increasingly common; however, interpretation of compositional data may not be straightforward. Natural gold is rarely homogenous. Alloy heterogeneity is present as microfabrics formed either during primary mineralization or by modification of pre-existing alloys by chemical and physical drivers during subsequent residence in either hypogene or surficial environments. In electron-probe-microanalysis (EPMA)-based studies, the combination of Cu, Hg, and Pd values and mineral inclusion suites may be diagnostic for source style of mineralization, but Ag alone is rarely sufficient. Gold characterization studies by laser-ablation-ICP mass spectrometry linked to both quadrupole and Time-of-Flight (ToF-MS) systems show that only Ag, Cu, and Hg form homogenous alloys with Au sufficiently often to act as generic discriminants. Where present, other elements are commonly distributed highly heterogeneously at the micron or submicron scale, either as mineral inclusions or in highly localized, but low concentrations. Drawing upon our own data derived from individual inspection and analyses of approximately 40,000 gold particles from 526 placer and in situ localities worldwide, we show that adequate characterization of gold from a specific locality normally requires study of a minimum of 150 particles via a two-stage approach comprising spatial characterization of compositional heterogeneity, plus crystallographic orientation mapping, that informs subsequent targeted acquisition of quantitative compositional data by EPMA and/or laser-ablation ICP-MS methods. Such data provide the platform to review current understanding of the genesis of gold particle characteristics, elevating future compositional studies from empirical descriptions to process-focused interpretations.

Representing crop rotations in life cycle assessment: a review of legume LCA studies - Marcela Porto Costa; David Chadwick; Sophie Saget; Robert M. Rees; Michael Williams; David Styles (The International Journal of Life Cycle Assessment, 2020)
Purpose There is an imperative to accurately assess the environmental sustainability of crop system interventions in the context of food security and climate change. Previous studies have indicated that the incorporation of legumes into cereal rotations could reduce overall environmental burdens from cropping systems. However, most life cycle assessment (LCA) studies focus on individual crops and miss environmental consequences of inter-annual crop sequence and nutrient cycling effects. This review investigates state-of-the-art representation of inter-crop rotation effects within legume LCA studies. Methods A literature review was undertaken, starting with a search for all peer-reviewed articles with combinations of ‘LCA’, ‘legumes’ and ‘rotations’ or synonyms thereof. In total, 3180 articles were obtained. Articles were screened for compliance with all of the following requirements: (i) reporting results based on LCA or life cycle inventory methodology; (ii) inclusion of (a) legume(s); (iii) the legume(s) is/are analysed within the context of a wider cropping system (i.e. rotation or intercropping). Seventy articles satisfying these requirements were analysed. Results and discussion We identified three broad approaches to legume LCA. Most studies involved simple attributional LCA disregarding important interactions across years and crops in rotations. N-fertilizer reduction through legume residue N carryover is either disregarded or the benefit is attributed to the following crop in such studies, whilst N leaching burdens from residues are usually attributed to the legume crop. Some studies applied robust allocation approaches and/or complex functional units to enable analysis of entire rotation sequences, accounting for nutrient cycling and break crop effects. Finally, a few studies applied consequential LCA to identify downstream substitution effects, though these studies did not simultaneously account for agronomic effects of rotational sequence changes. Conclusions We recommend that LCA studies for legume cropping systems should (i) evaluate entire rotations; (ii) represent nitrogen and ideally carbon cycling; (iii) for attributional studies, define at least two functional units, where one should encompass the multifunctional outputs of an entire rotation and the other should enable product footprints to be calculated; (iv) for CLCA studies, account for both agronomic changes in rotations and markets effects; (v) include impact categories that reflect hotspots for agricultural production.

Adapting Stand‐Alone Renewable Energy Technologies for the Circular Economy through Eco‐Design and Recycling - John Gallagher; Biswajit Basu; Maria Browne; Alan Kenna; Sarah McCormack; Francesco Pilla; David Styles (Journal of Industrial Ecology, 2019)
Summary Renewable energy (RE) technologies are looked upon favorably to provide for future energy demands and reduce greenhouse gas (GHG) emissions. However, the installation of these technologies requires large quantities of finite material resources. We apply life cycle assessment to 100 years of electricity generation from three stand‐alone RE technologies—solar photovoltaics, run‐of‐river hydro, and wind—to evaluate environmental burden profiles against baseline electricity generation from fossil fuels. We then devised scenarios to incorporate circular economy (CE) improvements targeting hotspots in systems’ life cycle, specifically (1) improved recycling rates for raw materials and (ii) the application of eco‐design. Hydro presented the lowest environmental burdens per kilowatt‐hour of electricity generation compared with other RE technologies, owing to its higher efficiency and longer life spans for main components. Distinct results were observed in the environmental performance of each system based on the consideration of improved recycling rates and eco‐design. CE measures produced similar modest savings in already low GHG emissions burdens for each technology, while eco‐design specifically had the potential to provide significant savings in abiotic resource depletion. Further research to explore the full potential of CE measures for RE technologies will curtail the resource intensity of RE technologies required to mitigate climate change.

Climate mitigation by dairy intensification depends on intensive use of spared grassland - David Styles; Alejandra Gonzalez‐Mejia; Jon Moorby; Andreas Foskolos; James Gibbons (Global Change Biology, 2018)
Milk and beef production cause 9% of global greenhouse gas ( GHG ) emissions. Previous life cycle assessment ( LCA ) studies have shown that dairy intensification reduces the carbon footprint of milk by increasing animal productivity and feed conversion efficiency. None of these studies simultaneously evaluated indirect GHG effects incurred via teleconnections with expansion of feed crop production and replacement suckler‐beef production. We applied consequential LCA to incorporate these effects into GHG mitigation calculations for intensification scenarios among grazing‐based dairy farms in an industrialized country ( UK ), in which milk production shifts from average to intensive farm typologies, involving higher milk yields per cow and more maize and concentrate feed in cattle diets. Attributional LCA indicated a reduction of up to 0.10 kg CO 2 e kg −1 milk following intensification, reflecting improved feed conversion efficiency. However, consequential LCA indicated that land use change associated with increased demand for maize and concentrate feed, plus additional suckler‐beef production to replace reduced dairy‐beef output, significantly increased GHG emissions following intensification. International displacement of replacement suckler‐beef production to the “global beef frontier” in Brazil resulted in small GHG savings for the UK GHG inventory, but contributed to a net increase in international GHG emissions equivalent to 0.63 kg CO 2 e kg −1 milk. Use of spared dairy grassland for intensive beef production can lead to net GHG mitigation by replacing extensive beef production, enabling afforestation on larger areas of lower quality grassland, or by avoiding expansion of international (Brazilian) beef production. We recommend that LCA boundaries are expanded when evaluating livestock intensification pathways, to avoid potentially misleading conclusions being drawn from “snapshot” carbon footprints. We conclude that dairy intensification in industrialized countries can lead to significant international carbon leakage, and only achieves GHG mitigation when spared dairy grassland is used to intensify beef production, freeing up larger areas for afforestation.

Development of a Risk Index for Use in Water Quality Monitoring - Lisa Jones; David Styles; Brian Kinsella; Antoin Lawlor; Ambrose Furey; Fiona Regan (Water Conservation Science and Engineering, 2017)

Climate regulation, energy provisioning and water purification: Quantifying ecosystem service delivery of bioenergy willow grown on riparian buffer zones using life cycle assessment - David Styles; Pål Börjesson; Tina D’Hertefeldt; Klaus Birkhofer; Jens Dauber; Paul Adams; Sopan Patil; Tim Pagella; Lars B. Pettersson; Philip Peck; Céline Vaneeckhaute; Håkan Rosenqvist (Ambio, 2016)

Inventory compilation for renewable energy systems: the pitfalls of materiality thresholds and priority impact categories using hydropower case studies - John Gallagher; David Styles; Aonghus McNabola; A. Prysor Williams (The International Journal of Life Cycle Assessment, 2015)